2020
DOI: 10.1128/jcm.01689-20
|View full text |Cite
|
Sign up to set email alerts
|

Serological Screening of Influenza A Virus Antibodies in Cats and Dogs Indicates Frequent Infection with Different Subtypes

Abstract: Influenza A viruses (IAVs) infect humans and a variety of other animal species. Infections with some subtypes of IAV were also reported in domestic cats and dogs. Besides animal health implications, close contact between companion animals and humans also poses a potential risk of zoonotic IAV infections. In this study, serum samples from different cat and dog cohorts were analyzed for IAV antibodies against 7 IAV subtypes, using three distinctive IAV-specific assays differing in IAV subtype-specific discrimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…There are also reports of occasional influenza cases in cats caused by other IAVs [16,50,51]. A recent study confirmed that the presence of antibodies to IAVs of both avian and human origin is not uncommon in European shelter cats [6]. Antibodies against H1, H3, H5, H7 and H9 were found in their sera.…”
Section: Low Pathogenic Iavsmentioning
confidence: 87%
See 3 more Smart Citations
“…There are also reports of occasional influenza cases in cats caused by other IAVs [16,50,51]. A recent study confirmed that the presence of antibodies to IAVs of both avian and human origin is not uncommon in European shelter cats [6]. Antibodies against H1, H3, H5, H7 and H9 were found in their sera.…”
Section: Low Pathogenic Iavsmentioning
confidence: 87%
“…In contrast, antigenic shift leads to the sudden emergence of a new subtype resulting from the exchange (reassortment) of RNA fragments between two or more IAV subtypes replicating at the same time in a host [ 4 ]. Well-recognised “mixing vessel” hosts for human IAVs include pigs and birds, but recent data suggest that dogs and cats might also potentially play such a role [ 5 , 6 ]. These new subtypes, which share pathogenic properties with their parental lineages and have a mixture of the surface antigens of the original strains, can be highly dangerous.…”
Section: Aetiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Such instance forewarns potential viral transmission through close contact between humans and their companion animals ( Belser et al, 2017 ). In addition, the fact that the respiratory tract of dogs harbors receptors for both avian-adapted and mammal-adapted influenza viruses ( Tate et al, 2014 ) and the increasing evidence of canine infection with swine, human, and avian IAVs of different subtypes ( Chen et al, 2018 ; Zhao et al, 2020 ) point toward a capacity for canines to serve as “mixing vessels” to generate novel gene constellations, which may lead to future pandemics in the human population.…”
Section: Discussionmentioning
confidence: 99%